The Influence of Business Capital, Business Opportunities, and Motivation on Community Entrepreneurial Interest - Irentina Sinaga; Nalom Siagian; Kepler Sinaga (Golden Ratio of Data in Summary, 2024)
This research aims to determine the influence of business capital, business opportunities and motivation on people's entrepreneurial interest through research with a quantitative approach. The research population was the entire community in Tanjungan village and the research sample consisted of 110 respondents. This research uses primary data and secondary data with a Likert scale questionnaire via Google Form. This research data was processed through structural model analysis (SEM) with the help of AMOS charts. The analysis in this research is validity test (CFA), reliability test, normality test, goodness of fit and hypothesis test. Based on the research results, Business Capital has a positive but not significant effect on the entrepreneurial interest of the Community at the Aek Natonang Tourist Attraction Location in Tanjungan Village, Simanindo District, Samosir Regency. Hypothesis test results, Business Capital CR/tcount is 1.787 < t table nα/2df = 1.964 and value p-value is 0.007 < α = 0.05. This means that Business Capital has a positive but not significant effect on Entrepreneurial Interest. Business Opportunity with a calculated CR/t value of 3.109 > CR/t table 1.964 and a p-value of 0.022 < α =0.05. So it can be concluded that Business Opportunities have a significant and positive influence on Community Entrepreneurial Interest at the Aek Natonang Tourist Attraction Location in Tanjungan Village, Simanindo District, Samosir Regency. Motivation with a calculated CR/t value of 1.978 > CR/t table 1.964 and a p-value of 0.035 < α= 0.05. So it can be concluded that motivation has a significant and positive effect on Community Entrepreneurial Interest at the Aek Natonang Tourist Attraction Location in Tanjungan Village, Simanindo District, Samosir Regency.